White-light emission based on a single component Sm(iii) complex and enhanced optical properties by doping methods. Issue 6 (11th January 2019) - Xu, Yuan-Yi; Chen, Peng; Gao, Ting; Li, Hong-Feng; Yan, Peng-Fei
Abstract : Six lanthanide complexes with enhanced tunable photoluminescence were designed and synthesized using codoping methods and single component white-light emission was achieved. Abstract : A new series of dinuclear lanthanide complexes, Ln2 (Hshi)2 DBM4 ·2DMF (Ln = Sm, Eu, Gd, Dy, Nd and Yb) were synthesized using H3 shi (H3 shi = salicylhydroxamic acid) and a β-diketonate ligand (DBM = dibenzoylmethanide). The two Ln(iii ) ions in the molecules are bridged by a salicylhydroxamic ligand with a rigid configuration. The structures of the isostructural complexes1–6 were determined by single-crystal X-ray crystallography. The optical properties of the complexes can be simply enhanced by doping methods. White-light emission materials can be obtained from a single component (Sm 3+ ) by adjusting the excitation wavelength. The lifetimes and quantum yields of the luminescence were also determined.